The successional dynamics of Acacia nilotica (L.) savanna - Skowno, Andrew L (Department of Biological Sciences, 2017)
Analysis of aerial photographs indicates that woody plant biomass has increased in Hluhluwe Game Reserve, KwaZulu Natal, over a relatively short period. Despite their slow growth rates, Eucleas and other broadleaf species are responsible for the majority of this increase. Nine sites were chosen to examine the recruitment patterns and sizeclass distributions of Euclea divinorum and E. racemosa. Analysis of the size-class distribution data suggests that recruitment of Eucleas is slightly higher below adult A. nilotica canopies than in adjacent interspaces. The number of seedlings is significantly higher below Acacia canopies than in open spaces. Size class data indicate that the largest Euclea individuals are found in open spaces and not below A. nilotica canopies. Because Eucleas have slower growth rates than A. nilotica, the large Eucleas may well have become established before the present A. nilotica stand. The data also indicate that A. karroo is replacing A. nilotica and that broadleaf species other than Eucleas are recruiting in both open and below canopy plots. I suggest A. nilotica adults only weakly facilitate the establishment of Eucleas and other broadleaved species, and that increase in woody vegetation is due to changes in the fire regime that allow suppressed broadleaf individuals to escape and become visible. This release may explain the rapid rate of encroachment by inherently slow growing species.